An argumentation activity for third-grade students: objects in the plates. (2nd January 2019) - Akbayrak, Kemal; Namdar, Bahadir
Abstract: The purpose of this study is to design an argumentation activity for third-grade students learning about the features defining matter. The research was carried out with seven students who enrolled in a tutoring program in a science and art center in the Eastern Black Sea region of Turkey during the academic year of 2017–2018. The activities were completed over four hours. First, the students were asked to make a claim using the available data, and write a justification supporting their claims. Second, they were asked to evaluate their friends' classifications of different objects. Third, they were asked to use reasoning to rebut the counterclaims provided by their peers. We found that the students used evidence while supporting their initial claims and rebutting the other students' claims. However, the students still had difficulties using evidence to justify their claims.